MORFOGENESIS ANGGREK (Anoectochilus formosanus) SECARA IN VITRO - L. D. Saputri; Sulastri Isminingsih; Andi Apriany Fatmawaty; F. Rachmawati (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2019)
ABSTRACTAnoectochilus formosanus is one species of Orchids, known as a “Jewel Orchids”and have been used as a folk medicine in China and Taiwan.The aim of this studywas to examine the response of using different types of explants and combination of growth regulators TDZ and BAP to morphogenesis of Anoectochilus formosanus Orchids by in vitro. The results showed that using different types of explants had very significant effect to the percentage of callus and shoot morphogenesis on 12 weeks after planting, the number of adventitious buds, adventitious shoot length, and callus diameter on three weeks until 12 weeks after planting. The best explant to callus morphogenesis was showing on shoot tip explant (50%) and to shoot morphogenesis was showing on auxillary buds and internode explant (100%). The best number of adventitious buds was observed in second internode explant with average number of shoots are 7.62 shoots. The best adventititous length was observed in axillary buds explant with average number of shoot length in 1.16 cm, and the best callus diameter was observed in shoot tip explant with average of diameter in 2.2 mm. The combination of plant growth regulator TDZ and BAP had a very significant effect to adventitious length on 10 weeks after planting, and a significant effect to adventitious length on 11 and 12 weeks after planting. The best adventitious length was observed on 0.25 mg L-1 TDZ + 0.75 mg L-1 BAP in 1.13 cm per explant on 12 weeks after planting. The best combination to callus and shoot morphogenesis was observed on 0.75 mg L-1 TDZ + 0.25 mg L-1 BAP. There was no interaction between used a different types of explant and combination plant growth regulator to morphogenesis Anoectochilus formosanus orchids by in vitro.